Commodus : An Emperor at the Crossroads - Hekster, O. (Dutch Monographs on Ancient History and Archaeology, 2002)
The emperor Commodus (AD 180-192) has commonly been portrayed as an insane madman, whose reign marked the beginning of the end of the Roman Empire. Indeed, the main point of criticism on his father, Marcus Aurelius, is that he appointed his son as his successor. Especially Commodus' behaviour as a gladiator, and the way he represented himself with divine attributes (especially those of Hercules), are often used as evidence for the emperor's presumed madness. However, this 'political biography' will apply modern interpretations of the spectacles in the arena, and of the imperial cult, to Commodus' reign. It will focus on the dissemination and reception of imperial images, and suggest that there was a method in Commodus' madness.